The Powers of the Constitutional Court in Light of the Constitutional Amendment of 2020 - Laouidji, Abdallah (Journal of Legal Studies and Researches, 2023)
The constitutional amendment of 2020 approved the Constitutional Court as a new mechanism for monitoring the constitutionality of laws as an alternative to the Constitutional Council. The constitution expanded the powers of this institution, as it enabled it to supervise organizations as well as interpret the provisions of the constitution.